SIRT1–SIRT7 in Diabetic Kidney Disease: Biological Functions and Molecular Mechanisms - Qi, Wenxiu; Hu, Cheng; Zhao, Daqing; Li, Xiangyan (Frontiers in Endocrinology, 2022)
Diabetic kidney disease (DKD) is a severe microvascular complication in diabetic patients and is one of the major causes of renal failure. The current clinical treatment methods for DKD are not completely effective, which suggests that we need to further explore the molecular mechanism of the pathological process of DKD, and is very urgent to improve and promote the treatment strategy. Sirtuins are class III histone deacetylases that play important roles in many biological functions, including DNA repair, apoptosis, cell cycle, oxidative stress, mitochondrial function, energy metabolism, lifespan, and aging. In the last decade, research on sirtuins and DKD has become more attractive and more extensive. Therefore, it is extremely important to summarize the relationship between DKD and sirtuins for increasing awareness of DKD to improve the cure rates. We found that miRNAs, lncRNAs, compounds or drugs that up-regulate sirtuins activity and expression level all play protective roles in renal function. Therefore, in this review, we summarize the biological functions, molecular targets, mechanisms and signaling pathways of SIRT1-SIRT7 in DKD models. Existing research conclusions prove that sirtuins have absolute potential as effective target for the clinical treatment of DKD. The purpose of this review is to lay a solid foundation for clinical research, and provide theoretical basis for slow down the development of clinical patients with DKD.